Domestic violence - Lawyers Collective (Bombay, India); Kali for Women (Organization) (New Delhi : Kali for women, 1992)
On legal protection in India for civil and criminal offences against women
Keywords: Family violence -- Law and legislation -- India; Abused wives -- Legal status, laws, etc. -- India; Wife abuse -- India